2003
DOI: 10.1023/b:fish.0000045722.44186.ee
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lipid level and vegetable oil on fatty acid metabolism in Atlantic salmon (Salmo salar L.) over the whole production cycle

Abstract: Changes in fatty acid metabolism in Atlantic salmon (Salmo salar) induced by vegetable oil (VO) replacement of fish oil (FO) and high dietary oil in aquaculture diets can have negative impacts on the nutritional quality of the product for the human consumer, including altered flesh fatty acid composition and lipid content. A dietary trial was designed to investigate the twin problems of FO replacement and high energy diets in salmon throughout the entire production cycle. Salmon were grown from first feeding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 45 publications
(26 reference statements)
5
64
1
Order By: Relevance
“…The activity of the LC-PUFA biosynthesis pathway was significantly lower in liver and intestine from salmon being fed EPA and DHA in the form of fish oil compared to fish fed vegetable oils that are devoid of LC-PUFA (Tocher et al, 1997(Tocher et al, , 2003c. There is also a significant correlation between the activity of the LC-PUFA biosynthetic pathway and dietary n-3 LC-PUFA levels (Tocher et al, 2003b).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the LC-PUFA biosynthesis pathway was significantly lower in liver and intestine from salmon being fed EPA and DHA in the form of fish oil compared to fish fed vegetable oils that are devoid of LC-PUFA (Tocher et al, 1997(Tocher et al, , 2003c. There is also a significant correlation between the activity of the LC-PUFA biosynthetic pathway and dietary n-3 LC-PUFA levels (Tocher et al, 2003b).…”
Section: Discussionmentioning
confidence: 99%
“…One that has gained significant interest in salmonid feeds is linseed oil. As it contains more than 50% of the fatty acids as linolenic acid (LNA,18:3n-3) it has been explored as a potential for increasing the content of n-3 HUFA in salmonid fish flesh (Tocher et al 2003a;Bendiksen and Jobling 2004).…”
Section: Norwegian Scientific Committee For Food Safetymentioning
confidence: 99%
“…A natural consequence of this is that increases in n-6 HUFA in PI following increased feeding of 18:2n-6 should cause major increases in the production of this series of eicosanoids. Indeed most available literature do point to this in salmonids while Norwegian Scientific Committee for Food Safety Vitenskapskomiteen for mattrygghet (VKM) 81 07/604 -final increases in n-3 HUFA or linseed oil (18:3n-3) will inhibit the production of n-6 eicosanoids (Ashton et al 1994;Bell et al 1996a;Balfry and Higgs 2001;Tocher et al 2003b;Gjøen et al 2004). The question then remains if increasing the n-6 PUFA in plant oil supplemented diets will enhance the immune response as seen in mammals and reduce the likelihood of infections.…”
Section: Effect Of the Oil Fraction On Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the present results suggested that juvenile Arctic charr are more efficient at retaining dietary DHA and/or the amount of DHA synthesised de novo is higher compared to adult Arctic charr. Tocher et al (2003) found that endogenous synthesis of DHA was higher in juvenile Atlantic salmon (parr) compared to older Atlantic salmon (smolt). During later stages of development, fish allocate energy to gonadal maturation (Izquiredo et al, 2001;Mourente and Odriozola, 1990;Wiegand 1996) and thus retention of DHA in somatic tissues may be reduced in sexually mature adults.…”
Section: Discussionmentioning
confidence: 95%